Comparison of Postoperative Outcomes of Patients Undergoing Total Hip and Total Knee Arthroplasty Following a Diagnosis of Dementia: A TriNetX Database Study - Andrea H. Johnson, MSN, CRNP; Jane C. Brennan, MS; Paul J. King, MD; Justin J. Turcotte, PhD, MBA; James H. MacDonald, MD (Arthroplasty Today, 2024)
Background: As life expectancy improves for patients with dementia, the demand for mobility-improving surgeries such as total joint arthroplasty (TJA) will increase. There is little research on patients with dementia undergoing TJA, although dementia has been shown to be a risk factor for complications. The purpose of this study is to compare postoperative outcomes of patients with dementia undergoing TJA at 90 days, 2 years, and 5 years. Methods: The TriNetX database was retrospectively queried for all patients undergoing total hip arthroplasty (THA) and total knee arthroplasty (TKA). Patients were divided into cohorts by preoperative diagnosis of dementia and propensity score matched. The following outcomes were evaluated between groups at 90 days, 2 years, and 5 years postoperatively: revision, resection arthroplasty, closed reduction (THA only), femur fracture plating, and prosthetic joint infection. Readmission and manipulation under anesthesia (TKA only) were evaluated at 90 days postoperatively. Univariate and multivariate analyses were performed. Results: After matching, there were no differences in demographics or comorbidities between groups. TKA (odds ratio [OR] = 1.75, 95% confidence interval [CI] 1.42-2.15, P < .001) and THA (OR = 2.17, 95% CI 1.92-2.45, P < .001) patients with dementia were more likely to be readmitted than patients without dementia. At 2 years (OR = 2.07, 95% CI 1.14-3.77, P = .015) and 5 years (OR = 2.14, 95% CI 1.32-3.48, P = .002) postoperatively, THA patients with dementia were more likely to have proximal femur fracture plating than patients without dementia. Conclusions: Patients undergoing THA with dementia had worse outcomes than patients undergoing THA without dementia and TKA with dementia. The overall rate of complications was low, and a diagnosis of dementia should not be an absolute contraindication to proceeding with TJA.